Avaliação da usabilidade de um website informativo para prevenção da transmissão vertical da sífilis por profissionais da saúde na atenção primária - Silva, Raylton Aparecido Nascimento (2023)
Introduction: All over the world, pregnant women are part of the group most concerned about infection by treponema pallidum, responsible for syphilis, due to the risk of transmission to the conceptus and the high incidence. In the world, currently, 1.5 million pregnant women are infected per year, indicating the need to implement preventive actions. Doctors and nurses can apply normative guidelines for the diagnosis, treatment and follow-up of pregnant women. Objective: To evaluate the usability of the website system with information for the diagnosis, treatment and monitoring of vertical transmission of Syphilis by health professionals who assist pregnant people. Models and techniques: Cross-sectional research, carried out in the city of Santa Maria (RS), with health professionals who assist pregnant women in Primary Health Care. Data collection took place from October to December 2022. An electronic form (Google forms) was used with the Scale System Usability (SUS) instrument and open questions, in person at the service or online. Results: the creation of a website with informative content on the topic of preventing congenital syphilis, which was validated by a committee of experts. professionals evaluated the website as best imaginable with a median of 90% (85-97.5) and there was no significant association with the profile of the participants. In the usability evaluation, 95.2% of the research participants indicated that they have expectations, motivation and ability to use the tool and that they would indicate the website to colleagues and academics in the area for use in continuing education. They indicated as facilitators the availability of internet access, the optimization of time and suggested the use in other actions besides being during prenatal consultations, also in family planning, in the puerperium and in individual consultations. Conclusion: The website is an adequate tool to be used with health professionals, this fact indicates that it can help in the qualification of the assistance provided to pregnant women.